2014
DOI: 10.1016/j.jtcvs.2013.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Impact and predictors of acute exacerbation of interstitial lung diseases after pulmonary resection for lung cancer

Abstract: Pulmonary resection for patients with lung cancer with interstitial lung diseases may provoke acute exacerbation at a substantially high rate and has high associated mortality. Surgical procedures that proved to be a risk factor for acute exacerbation should be chosen cautiously for these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
291
8
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(320 citation statements)
references
References 31 publications
17
291
8
4
Order By: Relevance
“…AE is an important negative prognostic factor for surgically resected lung cancer patients with interstitial lung disease (ILD). Sato et al (6) reported that AE occurred in 9.3% of surgically resected lung cancer patients with ILD, accounting for a mortality rate of 43.9%. They also identified the following independent risk factors for AE: Surgical procedures (wedge resection, lobectomy/segmentectomy, bilobectomy/pneumonectomy), male gender, history of exacerbation, pre-operative steroid use, elevated serum KL-6 levels (≥1,000 U/ml), appearance of UIP in the CT spectrum and reduced percentage of predicted vital capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AE is an important negative prognostic factor for surgically resected lung cancer patients with interstitial lung disease (ILD). Sato et al (6) reported that AE occurred in 9.3% of surgically resected lung cancer patients with ILD, accounting for a mortality rate of 43.9%. They also identified the following independent risk factors for AE: Surgical procedures (wedge resection, lobectomy/segmentectomy, bilobectomy/pneumonectomy), male gender, history of exacerbation, pre-operative steroid use, elevated serum KL-6 levels (≥1,000 U/ml), appearance of UIP in the CT spectrum and reduced percentage of predicted vital capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that CPFE patients have a significantly increased risk of lung cancer compared with patients with chronic obstructive pulmonary disease (COPD) or IPF alone (1,4,5). Post-operative acute exacerbation (AE) of interstitial lung disease in patients with lung cancer is associated with a high mortality rate (43.9%) (6). However, the clinical features and prognosis of patients with lung cancer and CPFE have remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological assessment of IP in the resected lung was performed, if possible. A diagnosis of AE was made based on clinical and radiologic findings using previously presented criteria for postoperative AE [4]. Briefly, the criteria were (1) onset within 30 days after pulmonary resection, (2) intensified dyspnea, (3) increased interstitial shadows in chest radiograph and chest CT images, (4) decreased arterial oxygen tension greater than 10 Torr under similar conditions, (5) no evidence of pulmonary infection, and (6) exclusion of alternative causes, such as cardiac failure, pulmonary embolism, or other identifiable causes of lung injury.…”
Section: Methodsmentioning
confidence: 99%
“…Acute exacerbation (AE) in patients with idiopathic interstitial pneumonia (IP), mostly comprised of idiopathic pulmonary fibrosis cases is a potentially fatal postoperative complication following lung surgery [1][2][3][4][5][6]. Patients with IP comprise 4-5 % of those with lung cancer who undergo such an operation, while AE occurs in 9-15 % of patients with idiopathic IP undergoing lung cancer resection and the rate of mortality in those is approximately 50 % [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation